Evaluation of different surface treatment methods on shear bond strength of orthodontic brackets on demineralized enamel. - Nazly Adeeb Yahya; Zana Qadir Omar (Erbil Dental Journal)
Background and Objective: One of the ordinary problems throughout orthodontic treatment is bracket debonding , which affect treatment course and results in increased treatment duration and more clinical time for bonding again of failed brackets This study aimed to evaluate the shear bond strength(SBS) of brackets bonded to demineralized enamel pretreated with fluoride varnish (3M),sodium hypochlorite NaClO 5% and low viscosity Icon Infiltrant resin (DMG)and laser ( YAG) with fluoride and evaluation of the adhesive remnant index (ARI) on the deboned bracket. Materials and method: A total of 65 human maxillary premolar teeth were assigned in to five groups (n=13) Groups. The surface of all groups were submitted to demineralized solution, and the first groups was the demineralized group (left with no treatment), second and third groups (demineralized) were treated with fluoride varnish 5% (Clinpro White Varnish, 3m ESPE) and 5.5% sodium hypochlorite NaClO, fourth and fifth group (demineralized) were treated with Infiltrate resin (Icon, DMG) and laser (Er,Cr:YSGG laser,Waterlase® iPlusTM). Shear bond strength(SBS) was evaluated by means of a universal testing machine, and Stereomicroscope was used to determine (ARI) at x20 magnification. Data were analyzed using the Statistical Package for Social Sciences (SPSS, version 22). Kruskal Wallis test was used to analyze the bond strength data and adhesive remnant index (ARI). Results: Notable difference was observed in the shear bond strength of all groups. The bond strength of the demineralized group, which treated by fluoride varnish 5% (Clinpro White Varnish, 3m ESPE) was significantly lower than the other groups. According to the (ARI) most samples in all groups show score 0 which means the failure zone inside demineralized enamel surface. Conclusion: Fluoride varnish, infiltrate resin (Icon, DMG) and laser were failed to improve SBS (shear bond strength) of brackets on demineralized teeth.